Expand (2x)² : Converting Product Square to Standard Form

Question

Insert the corresponding expression:

(2×x)2= \left(2\times x\right)^2=

Video Solution

Solution Steps

00:00 Simplify the following problem
00:03 In order to open parentheses with a multiplication operation and an outside exponent
00:07 Raise each factor to the power
00:11 Raise each factor to the power
00:16 This is the solution

Step-by-Step Solution

To solve the expression (2×x)2(2 \times x)^2, we'll follow these steps:

  • Step 1: Identify the base of the exponent, which is the product 2×x2 \times x.
  • Step 2: Apply the Power of a Product rule, which states that (ab)n=an×bn(ab)^n = a^n \times b^n.
  • Step 3: Distribute the exponent to both factors within the parentheses:

(2×x)2=22×x2(2 \times x)^2 = 2^2 \times x^2

Calculating 222^2 gives:

22=42^2 = 4

So, the expression simplifies to:

4×x24 \times x^2

Therefore, the correct expression is 22×x22^2 \times x^2.

This corresponds to Choice 2.

Answer

22×x2 2^2\times x^2